FRACTURE CHARACTERIZATION IN BASEMENT ROCKS USING BOREHOLE IMAGE LOGS AT DAYUNG FIELD, CORRIDOR BLOCK, SOUTH SUMATRA - JUANDI, DEDI
Naturally fractured reservoir in the basement rocks has well known by the oil and gas industry. Fractured reservoir can have dual porosity type such as conventional matrix and fracture porosity that can be formed by fractured activity. Both pore network type causing significant difficulties in order to describe the internal structure and fluid flow inside fractured reservoir. Naturally fractured reservoir in the basement rocks as a place for oil and gas in general formed in intensively fracture network instead of as pore matrix within the formation. Knowledge of distribution and fracture propagation within the basement reservoir is a key for improving the exploration and production management from this reservoir type. This research aimed for fracture reservoir characterization using borehole image log that can record the existing fracture. The characterization process consition of fracture type description, fracture attribute computation and measuring the fracture orientation as well as the bedding in order to model the fracture generation. Knowing the fracture generation model will give us the knowledge about the fracture propagation that will make easy further our exploration and production effort. The result of research suggests that the highly fracture density will be owned by the well which is located at the high strain and curvature zone such as the crest of anticline. The Highly fracture density will contribute to the highly porosity of reservoir.